Original Preparation of PEKK Dispersion for Coating by Transfer from a Chloroform Stable Dispersion to an Aqueous Stable Dispersion, by Emulsion/Solvent Evaporation. Issue 3 (3rd March 2016) - Giraud, Isabelle; Franceschi, Sophie; Perez, Emile; Lacabanne, C.; Dantras, E.
Abstract : In this work, aqueous dispersions of PolyEtherKetoneKetone (PEKK) oligomers were obtained by an emulsion/dispersion solvent evaporation technique. The PEKK oligomers were synthesized by a Friedel–Crafts acylation with a number average degree of polymerization of 4. The synthesized PEKK oligomers had very good thermal stability and spontaneously formed a stable dispersion of swollen micrometric fibers in chloroform. After sonication of the chloroform dispersion in water in the presence of sodium dodecyl sulfate (SDS) and evaporation, we obtained aggregated particles with a mean diameter between 120 and 160 nm, decreasing linearly with the PEKK concentration. The most stable dispersions were obtained with 0.5% wt of surfactant and, at a fixed concentration of SDS, the stability decreased when the PEKK concentration was increased. The different dispersions of PEKK in water were very stable and, after water evaporation, formed homogeneous films for high-performance coating. GRAPHICAL ABSTRACT: